Cerebral Metabolic Changes During Visuomotor Adaptation Assessed Using Quantitative fMRI - Foster, Catherine; Steventon, Jessica J.; Helme, Daniel; Tomassini, Valentina; Wise, Richard G. (Frontiers in Physiology, 2020)
The brain retains a lifelong ability to adapt through learning and in response to injury or disease-related damage, a process known as functional neuroplasticity. The neural energetics underlying functional brain plasticity have not been thoroughly investigated experimentally in the healthy human brain. A better understanding of the blood flow and metabolic changes that accompany motor skill acquisition, and which facilitate plasticity, is needed before subsequent translation to treatment interventions for recovery of function in disease. The aim of the current study was to characterise cerebral blood flow (CBF) and oxygen consumption (relative CMRO2) responses during performance of a serial reaction time task using calibrated fMRI conducted in 20 healthy participants which induces rapid motor adaptation. Regions of interest (ROIs) were defined from areas showing linearly decreasing task-induced BOLD and CBF responses. BOLD, CBF and relative CMRO2 responses were calculated for each block of the task. Motor and somatosensory cortices and the cerebellum showed statistically significant positive responses to the task compared to baseline, but with decreasing amplitudes of BOLD, CBF and CMRO2 response as the task progressed. In the cerebellum, there was a sustained positive BOLD response in the absence of a significant CMRO2 increase from baseline, for all but the first blocks. This suggests that the brain may continue to elevate the supply energy even after CMRO2 has reduced to near baseline levels. Relying on BOLD fMRI data alone in studies of plasticity may not reveal the nature of underlying metabolic responses and their changes over time. Calibrated fMRI approaches may offer a more complete picture of the energetic changes supporting plasticity and learning.